INVENTARISASI JAMUR DI TAMAN HUTAN RAYA (TAHURA) BERASTAGI KABUPATEN KARO, SUMATERA UTARA - RAHMADINA RAHMADINA (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2021)
This study aims to determine the types of mushrooms, mushroom identification methods, the benefits of mushrooms, and how to collect mushrooms which was carried out from August to November 2019 at the Berastagi Forest Park (TAHURA), Karo Regency, North Sumatra. The sampling site was taken towards the North where the typography of the field is partly flat, steep and hilly with an air temperature of 23°C. Geographically, this Forest Park is located at 001'16